2011
DOI: 10.1016/j.aju.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of donor and recipient variables on the long-term live-donor renal allograft survival in children

Abstract: ObjectiveWe aimed to analyse donor and recipient predictors of graft survival in children who received live-donor renal grafts.Patients and methodsThe study comprised 273 children who received live-donor renal transplants at our center between March 1976 and October 2010. The follow-up ranged from 6 months to 25 years. Donor variables included donor age, gender, donor/recipient body weight ratio (DR BWR), ABO blood groups, human leukocyte antigen, and DR mismatching. Donor-specific problems, e.g., ischemia tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The difference between the findings of this present study and these previous studies could be linked to differences in sample size (number of graft failures observed), year of transplant, duration of follow-up and method of data analysis. Nevertheless, it is noteworthy that the significant predictors of GS observed in this study are in agreement with previous studies (11, 1618, 34, 35, 37, 38).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The difference between the findings of this present study and these previous studies could be linked to differences in sample size (number of graft failures observed), year of transplant, duration of follow-up and method of data analysis. Nevertheless, it is noteworthy that the significant predictors of GS observed in this study are in agreement with previous studies (11, 1618, 34, 35, 37, 38).…”
Section: Discussionsupporting
confidence: 93%
“…GF rates were computed as the ratio of the number of failed grafts to patient-years (PY) of follow-up and expressed as failure rates per 1,000 PY. Predictor variables or covariates for inclusion in this study were identified from literature using factors shown to significantly influence graft survival (1618).…”
Section: Methodsmentioning
confidence: 99%
“…The renal transplantation at our center was from living donor, majority from LRD (parents). Living donor transplant is reported to have better survival outcomes for pediatric recipients irrespective of donor age and should be recommended whenever possible . Immunosuppression protocols followed at our center are in accordance with the current practices and guidelines followed across the world…”
Section: Discussionmentioning
confidence: 92%
“…Living donor transplant is reported to have better survival outcomes for pediatric recipients irrespective of donor age and should be recommended whenever possible. 13,17,18 Immunosuppression protocols followed at our center are in accordance with the current practices and guidelines followed across the world. 12,13 Most recipients in our study had a negative history of post-trans- The graft survival rates observed at our center were 96.7% probabilities for recipients from LRD were 94%, 83%, and 77% at 1, 5, and 7 years post-transplant, respectively.…”
Section: Effect Of Transplantation On Renal Functionmentioning
confidence: 99%
“…Jacobs et al [ 11 ] compared graft survival between male and female transplant recipients at one- and three-years post-transplantation. Wafa et al [ 12 ] compared graft survival between male and female recipients at five- and 10- years post-transplantation. Both studies found no significant difference in short- and long-term graft survivals between male and female transplant recipients, also showing no significant difference between graft survival in transplant recipients who were the same gender as the donor and transplant recipients who were of a opposite gender as their donor.…”
Section: Resultsmentioning
confidence: 99%